Designing Decision Support System for Midwifery Students’ Tuition Fees Problem - Chandrawati Putri Wulandari; Aryo Pinandito (International Journal of Innovation in Enterprise System, 2021)
Education is an essential need and an important element to create a broad-minded youth. While in Indonesia, the rate of tuition fees is still imbalanced with the economic rate. Thus, many people decided to discontinue their higher education. Decision making plays an important role to manage organizations, including in educational institutions, as one of the main duties in managerial is making decisions. This study took place in a midwifery academy in Malang. In response to this situation, the academy has a policy to alleviate students by paying the tuition fees in instalments. However, many students are in arrears as the result of this policy. Thus, management needs to take some consideration before making a decision toward the problem. Those considerations require high accuracy and time consuming to process information that support decision making. Currently, the decision-making process in this academy is still semi-automated, in which some processes are still done manually, which affect longer time to make decisions, and the accuracy of calculations could not be fully guaranteed. According to this condition, the purpose of this research is to design a decision support system that enables us to process information for decision making and to offer decision alternatives for decision makers. This research employs Systems Development Life Cycle (SDLC) with a decision table as a method to create decision alternatives. The prototype was developed using Visual Studio C#.Net. The result shows that by using the proposed prototype of DSS, decision makers can reduce 5-10 minutes of decision making process compared to the old semi-automated system which still required manual calculation and data collection and analysis before making the decision. A complete data and more detailed parameters for decision criteria are required to implement the proposed prototype of DSS in the institution with more objective consideration in the decision making process as the future work.